(untitled) (Fiep Bulletin - online, 2016)
This paper reports findings of an experimental study about the effects of technical approach and TGfU on game skills, knowledge and game performance in basketball. Two groups of 10- to 11-year-old students participated in the study. A control group was taught by the technical approach and an experimental group by TGfU for 8 weeks. Game skills were measured by Under basket shot test, Dribbling test and Push pass for accuracy test. Procedural and declarative knowledge was assessed by a written test and game performance was assessed by GPAI in 3-3 basketball. Wilcoxon’s T-test and Man-Whitney’s U-test were used to evaluate the data. As a result both groups improved passing and dribbling skills (p<0.05 or p<0.01) but only the experimental group improved shooting skills (p<0.05). However there were no significant differences found between the groups’ improvement of game skills (p<0.05). Further analysis of the data showed that the experimental group was generally more successful in the knowledge test comparing to the control group (p<0.05). When rules and tactics were evaluated separately there were not found any significant differences between the groups (p<0.05). Even though we did not find significant differences between groups’ procedural and declarative knowledge at least the experimental group achieved better percentage of both. Additionally the experimental group showed better game performance compared to the control group (p<0.05). To conclude it seems that TGfU is more efficient approach to teaching basketball than the technical approach nevertheless a deeper exploration is needed indeed. Simultaneously motivation and engagement of students should be considered as well.